Diseño de una estrategia de participación ciudadana en los presupuestos municipales de la región la libertad - Aguilar Cruz, Genaro Alfredo (2015)
The objective of the research was to design a strategy for citizen participation in municipal budgets being population La Libertad region. Whereas as a statement of problem How to design a strategy for citizen participation in municipal budgets in the region Freedom enable them to strengthen the formulation of the municipal budget ?, considering the hypothesis that the design itself strengthens the process of formulation of municipal budget because in it the civil society and grassroots organizations involved. The research sample was evaluated for the district municipality of Paiján, Ascope province, La Libertad region. The method used was descriptive, explanatory and analytical method. The technique used was the interview and consultation with experts, mayors and city managers. The most important and momentous results is that participatory budgeting is not a process of citizenship, it is a tool that feeds citizens to corporate goals are achieved. We conclude that local governments through the decentralization process and using management tools become promoters of integral and sustainable development of their jurisdictions.